Reconstruction of total grain size distribution of the climactic phase of a long-lasting eruption: the example of the 2008-2013 Chaitén eruption - Pyle, D; Alfano, F; Bonadonna, C; Watt, S; Connor, C; Volentik, A (Springer Verlag, 2016)
The 2008-2013 eruption of Chaitén volcano (Chile), was a long-lasting eruption whose climactic phase (May 6th 2008) produced a sub-Plinian plume, with height ranging between 14 to 20 km, that dispersed to the NE, reaching the Atlantic coast of Argentina. The erupted material was mainly of lithic origin (77 wt%), resulting in a uni-modal Total Grain-Size Distribution (TGSD) dominated by coarse ash (77 wt%), with Md of 2.7 and  of 2.4. Lapilli clasts (> 2 mm) dominate the proximal deposit within ~20 km of the vent, while coarse (63 m - 2 mm) and fine ash (<63 m) sedimented as far as 800 km from vent, generating mostly poly-modal grain-size distributions across the entire deposit. Given that most of the mass is sedimented in proximal areas, results show that possible contributions of later explosive events to the thickness of the distal deposit where layers are less distinguishable (>400 km) do not significantly affect the determination of the TGSD. In contrast, gaps in data sampling in the medial deposit (in particular the gap between 50 and 350 km from vent, that coincides with shifts in sedimentation regimes) have large impacts on estimates of TGSD. Particle number distribution for this deposit is characterized by a high power-law exponent (3.0) following a trend very similar to the vesicle size distribution in the juvenile pyroclasts. Although this could be taken to indicate a bubble- driven fragmentation process, we suggest that fragmentation was more likely the result of a shear-driven process, because of the predominance of non-vesicular products (lithics and obsidians) and the large fraction of coarse ash in the TGSD.